Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the system of equations
[tex]\[ \begin{cases} 7x - 4y = -8 \\ y = \frac{3}{4}x - 3 \end{cases} \][/tex]
we follow these steps:
### 1. Substitute [tex]\( y \)[/tex] from the second equation into the first equation.
Given the second equation:
[tex]\[ y = \frac{3}{4}x - 3 \][/tex]
Substitute this expression for [tex]\( y \)[/tex] in the first equation:
[tex]\[ 7x - 4\left(\frac{3}{4}x - 3\right) = -8 \][/tex]
### 2. Simplify and solve for [tex]\( x \)[/tex].
First, distribute the [tex]\(-4\)[/tex]:
[tex]\[ 7x - 4 \left(\frac{3}{4}x\right) + 4 \cdot 3 = -8 \][/tex]
[tex]\[ 7x - 3x + 12 = -8 \][/tex]
[tex]\[ 4x + 12 = -8 \][/tex]
Subtract 12 from both sides:
[tex]\[ 4x = -8 - 12 \][/tex]
[tex]\[ 4x = -20 \][/tex]
Divide by 4:
[tex]\[ x = -5 \][/tex]
### 3. Substitute [tex]\( x = -5 \)[/tex] back into the second equation to find [tex]\( y \)[/tex].
Using [tex]\( y = \frac{3}{4}x - 3 \)[/tex], substitute [tex]\( x = -5 \)[/tex]:
[tex]\[ y = \frac{3}{4}(-5) - 3 \][/tex]
[tex]\[ y = -\frac{15}{4} - 3 \][/tex]
[tex]\[ y = -\frac{15}{4} - \frac{12}{4} \][/tex]
[tex]\[ y = -\frac{27}{4} \][/tex]
[tex]\[ y = -6.75 \][/tex]
### 4. Identify the closest approximate solution.
This means the solution to the system of equations is:
[tex]\[ (x, y) = (-5, -6.75) \][/tex]
Among the given options, we need to find the closest approximation to [tex]\( -6.75 \)[/tex]:
- [tex]\((-5, -7.2)\)[/tex]
- [tex]\((-5, -6.8)\)[/tex]
- [tex]\((-5, -6.2)\)[/tex]
- [tex]\((-5, -5.9)\)[/tex]
The value [tex]\( -6.75 \)[/tex] is closest to [tex]\( -6.8 \)[/tex].
### Conclusion:
The closest approximate solution to the system of equations is:
[tex]\[ \boxed{(-5, -6.8)} \][/tex]
[tex]\[ \begin{cases} 7x - 4y = -8 \\ y = \frac{3}{4}x - 3 \end{cases} \][/tex]
we follow these steps:
### 1. Substitute [tex]\( y \)[/tex] from the second equation into the first equation.
Given the second equation:
[tex]\[ y = \frac{3}{4}x - 3 \][/tex]
Substitute this expression for [tex]\( y \)[/tex] in the first equation:
[tex]\[ 7x - 4\left(\frac{3}{4}x - 3\right) = -8 \][/tex]
### 2. Simplify and solve for [tex]\( x \)[/tex].
First, distribute the [tex]\(-4\)[/tex]:
[tex]\[ 7x - 4 \left(\frac{3}{4}x\right) + 4 \cdot 3 = -8 \][/tex]
[tex]\[ 7x - 3x + 12 = -8 \][/tex]
[tex]\[ 4x + 12 = -8 \][/tex]
Subtract 12 from both sides:
[tex]\[ 4x = -8 - 12 \][/tex]
[tex]\[ 4x = -20 \][/tex]
Divide by 4:
[tex]\[ x = -5 \][/tex]
### 3. Substitute [tex]\( x = -5 \)[/tex] back into the second equation to find [tex]\( y \)[/tex].
Using [tex]\( y = \frac{3}{4}x - 3 \)[/tex], substitute [tex]\( x = -5 \)[/tex]:
[tex]\[ y = \frac{3}{4}(-5) - 3 \][/tex]
[tex]\[ y = -\frac{15}{4} - 3 \][/tex]
[tex]\[ y = -\frac{15}{4} - \frac{12}{4} \][/tex]
[tex]\[ y = -\frac{27}{4} \][/tex]
[tex]\[ y = -6.75 \][/tex]
### 4. Identify the closest approximate solution.
This means the solution to the system of equations is:
[tex]\[ (x, y) = (-5, -6.75) \][/tex]
Among the given options, we need to find the closest approximation to [tex]\( -6.75 \)[/tex]:
- [tex]\((-5, -7.2)\)[/tex]
- [tex]\((-5, -6.8)\)[/tex]
- [tex]\((-5, -6.2)\)[/tex]
- [tex]\((-5, -5.9)\)[/tex]
The value [tex]\( -6.75 \)[/tex] is closest to [tex]\( -6.8 \)[/tex].
### Conclusion:
The closest approximate solution to the system of equations is:
[tex]\[ \boxed{(-5, -6.8)} \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.